Pathways to professionalism? Quality improvement, care pathways, and the interplay of standardisation and clinical autonomy. Issue 8 (21st June 2017) - Martin, Graham P.; Kocman, David; Stephens, Timothy; Peden, Carol J.; Pearse, Rupert M.
Abstract: Care pathways are a prominent feature of efforts to improve healthcare quality, outcomes and accountability, but sociological studies of pathways often find professional resistance to standardisation. This qualitative study examined the adoption and adaptation of a novel pathway as part of a randomised controlled trial in an unusually complex, non‐linear field – emergency general surgery – by teams of surgeons and physicians in six theoretically sampled sites in the UK. We find near‐universal receptivity to the concept of a pathway as a means of improving peri‐operative processes and outcomes, but concern about the impact on appropriate professional judgement. However, this concern translated not into resistance and implementation failure, but into a nuancing of the pathways‐as‐realised in each site, and their use as a means of enhancing professional decision‐making and inter‐professional collaboration. We discuss our findings in the context of recent literature on the interplay between managerialism and professionalism in healthcare, and highlight practical and theoretical implications.